The impact of living arrangements on dietary patterns among older adults: the mediating effects of loneliness and anxiety - Hu, Yaping; Xiao, Jiangyan; Li, Xiaoxiao (Frontiers in Public Health, 2025)
Using data from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS), this study examines the relationship between living arrangements and dietary patterns among older adults aged 60 years and above. Linear regression and quantile regression models were employed to investigate the effects of living arrangements on dietary patterns, while the mediating roles of loneliness and anxiety were tested using the bootstrap method. The empirical results show that, after controlling for demographic and other characteristic variables, living arrangements have a significant positive impact on the dietary patterns of older adults. Compared with those living alone, older adults who live with family (β = 0.838) or in institutional settings (β = 1.378) exhibit healthier dietary patterns, with the strongest effect observed among those living in institutions. Furthermore, loneliness and anxiety significantly mediate the relationship between living arrangements and dietary patterns, with loneliness exhibiting a stronger mediating effect (β = 0.0117) than anxiety (β = 0.0037). These findings suggest that living arrangements positively influence older adults’ dietary patterns by reducing loneliness and anxiety. To better implement healthy aging strategies and enhance the overall health of older adults, communities and governments should place greater emphasis on addressing the psychological wellbeing of older adults, providing targeted interventions to optimize their lifestyles and improve their overall health.